African Americans Have Differences in CSF Soluble TREM2 and Associated Genetic Variants. (April 2021) - Schindler, Suzanne E.; Cruchaga, Carlos; Joseph, Amulya; McCue, Lena; Farias, Fabiana H.G.; Wilkins, Consuelo H.; Deming, Yuetiva; Henson, Rachel L.; Mikesell, Robert J.; Piccio, Laura; Llibre-Guerra, Jorge J.; Moulder, Krista L.; et al.
Abstract : Objective: To evaluate for racial differences in triggering receptor expressed on myeloid cells 2 (TREM2), a key immune mediator in Alzheimer disease, the levels of CSF soluble TREM2 (sTREM2), and the frequency of associated genetic variants were compared in groups of individuals who self-reported their race as African American (AA) or non-Hispanic White (NHW). Methods: Community-dwelling older research participants underwent measurement of CSF sTREM2 concentrations and genetic analyses. Results: The primary cohort included 91 AAs and 868 NHWs. CSF sTREM2 levels were lower in the AA compared with the NHW group (1, 336 ± 470 vs 1, 856 ± 624 pg/mL, p < 0.0001). AAs were more likely to carry TREM2 coding variants (15% vs 3%, p < 0.0001), which were associated with lower CSF sTREM2. AAs were less likely to carry the rs1582763 minor allele (8% vs 37%, p < 0.0001), located near MS4A4A, which was associated with higher CSF sTREM2. These findings were replicated in an independent cohort of 23 AAs and 917 NHWs: CSF sTREM2 levels were lower in the AA group ( p = 0.03), AAs were more likely to carry coding TREM2 variants (22% vs 4%, p = 0.002), and AAs were less likely to carry the rs1582763 minor allele (16% vs 37%, p = 0.003). Conclusions: On average, AAs had lower CSF sTREM2 levels compared with NHWs, potentially because AAs are more likely to carry genetic variants associated with lower CSF sTREM2 levels. Importantly, CSF sTREM2 reflects TREM2-mediated microglial activity, a critical step in the immune response to amyloid plaques. These findings suggest that race may be associated with risk for genetic variants that influence Alzheimer disease–related inflammation.